WWP1 Deficiency Alleviates Cardiac Remodeling Induced by Simulated Microgravity - Zhong, Guohui; Zhao, Dingsheng; Li, Jianwei; Liu, Zifan; Pan, Junjie; Yuan, Xinxin; Xing, Wenjuan; Zhao, Yinglong; Ling, Shukuan; Li, Yingxian (Frontiers in Cell and Developmental Biology, 2021)
Cardiac muscle is extremely sensitive to changes in loading conditions, the microgravity during space flight can cause cardiac remodeling and function decline. At present, the mechanism of microgravity-induced cardiac remodeling remains to be revealed. WW domain-containing E3 ubiquitin protein ligase 1 (WWP1) is an important activator of pressure-overload induced cardiac remodeling by stabilizing disheveled segment polarity proteins 2 (DVL2) and activating CaMKII/HDAC4/MEF2C axis. However, the role of WWP1 in the cardiac remodeling induced by microgravity is unknown. The purpose of this study was to determine whether WWP1 was also involved in the regulation of cardiac remodeling caused by microgravity. Firstly, we detected the expression of WWP1 and DVL2 in the heart from mice and monkeys after simulated microgravity using western blotting and Immunohistochemistry. Secondly, WWP1 knockout (KO) and wild type mice were subjected to hindlimb unloading (HU) to simulate microgravity effect. We assessed the cardiac remodeling in morphology and function through histological analysis and echocardiography. Finally, we detected the phosphorylation level of CaMKII and HDAC4 in the heart from WT and WWP1 KO mice after HU. The results revealed the increased expression of WWP1 and DVL2 in the hearts both from mice and monkeys after simulated microgravity. WWP1 deficiency protected against simulated microgravity-induced cardiac atrophy and function decline. Histological analysis demonstrated WWP1 KO inhibited the decreases in the size of individual cardiomyocytes of mice after hindlimb unloading. WWP1 KO can inhibit the activation of DVL2/CaMKII/HDAC4 pathway in hearts of mice induced by simulated microgravity. These results demonstrated WWP1 as a potential therapeutic target for cardiac remodeling and function decline induced by simulated microgravity.